Wroxeter, the Cornovii and the urban process : final report on the Wroxeter Hinterland project, 1994-1997. - White, Roger H., (Archaeopress, 2013)
In the mid 1990s, the site of the Roman city of Viroconium Cornoviorum at Wroxeter, Shropshire, was subjected to one of the most intensive campaigns of geophysical survey ever carried out on a Roman town. The result was a complete plan of the city using magnetometry but also significant deployment of other technologies including resistance, GPR and more experimental technologies. Since that time, geophysical survey has continued intermittently, using the site as a geophysical laboratory. This volume reports on the archaeological interpretation of this work, marrying the extensive and nuanced geophysical data with a detailed analysis of the existing aerial photographic record created by Arnold Baker during the 1950s to 1980s.